2019
DOI: 10.1073/pnas.1900774116
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of OSCA1.2 from Oryza sativa elucidates the mechanical basis of potential membrane hyperosmolality gating

Abstract: Sensing and responding to environmental water deficiency and osmotic stresses are essential for the growth, development, and survival of plants. Recently, an osmolality-sensing ion channel called OSCA1 was discovered that functions in sensing hyperosmolality inArabidopsis. Here, we report the cryo-electron microscopy (cryo-EM) structure and function of an OSCA1 homolog from rice (Oryza sativa; OsOSCA1.2), leading to a model of how it could mediate hyperosmolality sensing and transport pathway gating. The struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…CALCIUM-PERMEABLE STRESS-GATED CATION CHANNEL1 (CSC1)/OSCA1.2 is a homolog in the OSCA family and has been reported as a hyperosmolality-gated calcium-permeable channel protein (Hou et al, 2014). CSC1/ OSCA1.2 also mediated calcium fluxes in plant cells in response to osmotic stress conditions, although the detailed function of CSC1/OSCA1.2 in plant tissues remains unclear (Liu et al, 2018;Maity et al, 2019).…”
Section: Local Signals That Mediate Dehydration Stress Responses and mentioning
confidence: 99%
“…CALCIUM-PERMEABLE STRESS-GATED CATION CHANNEL1 (CSC1)/OSCA1.2 is a homolog in the OSCA family and has been reported as a hyperosmolality-gated calcium-permeable channel protein (Hou et al, 2014). CSC1/ OSCA1.2 also mediated calcium fluxes in plant cells in response to osmotic stress conditions, although the detailed function of CSC1/OSCA1.2 in plant tissues remains unclear (Liu et al, 2018;Maity et al, 2019).…”
Section: Local Signals That Mediate Dehydration Stress Responses and mentioning
confidence: 99%
“…Previous studies of Arabidopsis and rice have shown that OSCA family members contain DUF221 domain and have been identified to contain 15 and 11 members, respectively, with multiple genes associated with osmotic stress [13,26]. Each OSCA protein in the Arabidopsis and rice genomes contained 11 transmembrane domains [27,28]. In contrast, nine ZmOSCAs contained 9-11 transmembrane domains, and ZmOSCA1.1a and ZmOSCA3.1 proteins contained only four and two transmembrane domains, respectively (Table 1), which indicates that ZmOSCAs had experienced greater genetic variation during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The ion permeation path of most MSCs, including MscL and MscS 8 from bacteria, NOMPC 9 from fly, and TRAAK 10 and Piezo 11,12 from mammal, are along the symmetric axis. The dimeric TMEM120A is reminiscent of OSCAs [13][14][15][16] from plant, whose ion permeation path are along each protomer. Although TMEM120A shows the ability to permeate ions as measured in bilayer system, our results indicate TMEM120A does not response to poking or stretch mechanical stimuli in heterologous expression system.…”
Section: Discussionmentioning
confidence: 99%